Teachers’ Attitudes towards Translanguaging in Indonesian EFL Classrooms - Khairunnisa, Khairunnisa; Lukmana, Iwa (Jurnal Penelitian Pendidikan, 2020)
This study aims to investigate the attitudes towards translanguaging in EFL classrooms by 50 English language teachers. The present study employed quantitative descriptive. A survey was administered to the teachers to gauge information regarding the importance of translanguaging use and the frequency with which these teachers felt it was practiced in the classroom. The survey was collected through questionnaire that included multiple-choice and Likert scale questions. The findings revealed that Indonesian EFL teachers showed positive attitude towards the use of translanguaging in their classrooms. Most of them considered the incorporation of Indonesian language and local language are beneficial in EFL classrooms. It is also discovered that Indonesian EFL teachers were flexibly use translanguaging to facilitate students’ learning. Nonetheless, this study is limited to teachers’ attitudes. Hence, further study is needed to observe translanguaging practices in Indonesian EFL classrooms.